Motherhood and Cultural Expectations - An Autoethnography on Parenting a Child with Dyspraxia - Sarathy, Muthupon (2017)
The purpose of this dissertation is to explore the impact of cultural expectations about motherhood and how it affects parenting a child with a disability. Culture is part of the fabric of every society. It shapes the way things are done and our understanding of why this should be so. There is a very close connection between parenting and cultural attitudes and it is well-documented that the ways parents care for their children is shaped by their cultural beliefs and values. The methodology of autoethnography was used to explore my journey as an Indian mother of a child with dyspraxia and my mothering experience. Data was gathered for this research from my memory and reflective journals. The autoethnographic stories were written after remembering and recollecting from my memory with an emphasis on experiences that affected my life as a mother. Data analysis and interpretation involved focusing in and out of the social and personal realm, alternating between self and others, and sinking in and emerging out of the labyrinths of data. I have attempted to better understand how Indian cultural expectations have affected my personal experiences and expectations of motherhood by telling and reflexively analysing my stories. This research has made me realise the power and pervasiveness of cultural expectations and dominant ideologies of motherhood in my life and how they have shaped and influenced my thoughts and action in parenting a child with dyspraxia. The implications and suggestions for professionals and mothers, based on my experiences, are also provided. The role of the father, the society and the media in assisting children with disabilities and their families have also been discussed.